Trends and predictions of malnutrition and obesity in 204 countries and territories: an analysis of the Global Burden of Disease Study 2019 - Chong, Bryan; Jayabaskaran, Jayanth; Kong, Gwyneth; Chan, Yiong Huak; Chin, Yip Han; Goh, Rachel; Kannan, Shankar; Ng, Cheng Han; Loong, Shaun; Kueh, Martin Tze Wah; Lin, Chaoxing; Anand, Vickram Vijay; et al. (EClinicalMedicine, 2023)
Malnutrition and obesity are interdependent pathologies along the same spectrum. We examined global trends and projections of disability-adjusted life years (DALYs) and deaths from malnutrition and obesity until 2030. Using data from the 2019 Global Burden of Disease study involving 204 countries and territories, trends in DALYs and deaths were described for obesity and malnutrition from 2000 to 2019, stratified by geographical regions (as defined by WHO) and Socio-Demographic Index (SDI). Malnutrition was defined according to the 10th revision of International Classification of Diseases codes for nutritional deficiencies, stratified by malnutrition type. Obesity was measured via body mass index (BMI) using metrics related to national and subnational estimates, defined as BMI ≥25 kg/m2. Countries were stratified into low, low-middle, middle, high-middle, and high SDI bands. Regression models were constructed to predict DALYs and mortality up to 2030. Association between age-standardised prevalence of the diseases and mortality was also assessed. In 2019, age-standardised malnutrition-related DALYs was 680 (95% UI: 507–895) per 100,000 population. DALY rates decreased from 2000 to 2019 (−2.86% annually), projected to fall 8.4% from 2020 to 2030. Africa and low SDI countries observed highest malnutrition-related DALYs. Age-standardised obesity-related DALY estimates were 1933 (95% UI: 1277–2640). Obesity-related DALYs rose 0.48% annually from 2000 to 2019, predicted to increase by 39.8% from 2020 to 2030. Highest obesity-related DALYs were in Eastern Mediterranean and middle SDI countries. The ever-increasing obesity burden, on the backdrop of curbing the malnutrition burden, is predicted to rise further. None.